Rancang Bangun Sistem Presensi Siswa Menggunakan QR Code Pada SMA Negeri 10 Pekanbaru - Dinda Qoernia Jelita; Salhazan Nasution (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Attendance at SMA Negeri 10 Pekanbaru still done manually with an attendance book which then calls the names of students one by one to record their attendance which is carried out by each subject on one day by the teacher. This gives the teacher difficulty in recapitulating student attendance data due to damaged data, missing attendance lists and irrelevance of data. Therefore, a student presence system was designed and built using an Android-based QR code. Presence recapitulation is managed by the admin via the web and can be seen by parents of students. The system divided into 2, namely the android application for teachers to attendance and parents to see the history of student attendance and also the web for admin to manage all data. In the application, the teacher can perform presence by scanning the QR code that is owned by students or doing attendance manually. Parents through the android application will get notification of student attendance and can view attendance history through a certain date range. Admin can manage all data via the web. Usability testing that has been carried out by distributing USE questionnaires and calculated using a Likert scale results in 88.3% which is very satisfying in category. Keywords: attendance, android application, QR code, USE questionnaire